Uma abordagem de potencial e massa efetiva e a descrição de espaço de fase quântico para tratar sistemas de spins: Caracterizando o tunelamento de spin e propriedades da molécula de Fe8 - Silva, E. C [UNESP] (2009)
We have used an angle-based description and the quantum discrete phase space formalism to characterize Fe8 cluster properties. Through the angle-based approach we have calculated the the ground state barrier height, the energy splitting of the two lowest levels, the crossover temperature, the matching and the saturation magnetic field intensities. With the quantum phase space approach we also have used the energy splitting in order to study the spin tunneling of the lowest energy levels, a qualitative and a quantitative way to show the correlations between the angle and angular momentum variables via the Wigner and Husimi functions